Stress among anaesthetic trainees in Universiti Sains Malaysia - Sze, Ting Mei (2020)
Anaesthesia training is stressful and challenging. Stress can lead to potential burnout. This study was designed to investigate the prevalence of high stress and factors causing stress among anaesthetic trainees in Universiti Sains Malaysia (USM). A cross-sectional study design was conducted among anaesthetic trainees in USM. Data was collected by using paper or online questionnaire which was distributed to all anaesthetic trainees in USM. The survey consists of three parts, which includes sociodemographic and anaesthesia training characteristics, Perceived Stress Scale-10 (PSS-10), and Postgraduate Stressor Questionnaire (PSQ). Ninety-seven anaesthetic trainees participated in this study. Prevalence of high perceived stress was 47.4% (95% CI = 35.1%, 54.8%). Major stressors were exams, amount of knowledge to cover, and fear of making errors which could lead to serious consequences. Academic burden and performance pressure are the primary sources of stress in anaesthetic trainees in USM. Recognition of risk factors for stress and adaptive coping techniques are essential to the health and wellbeing of trainees.